Phytochemical Isolation And Standardization Of Orthosiphon Stamineus Benth. Leaf Extract From Different Locations And Selected Antioxidant And Toxicity Studies - Mughni, Nur Farah Amalina (2014)
This study aimed to standardize Orthosiphon stamineus extract from ten different locations throughout Peninsular Malaysia that includes pharmacognosical tests, chemical profile and biological activity (antioxidant and toxicity using a brine shrimp bioassay). Gravimetric analysis, heavy metal limit and microbial limit test were done on the dried leaf powder to determine the quality and safety of the raw material. Energy, carbohydrate, protein and fat content were estimated in all samples and the results (per 1g of raw material) were in the range of 305-339 kcal, 53.1-59.9 g, 12.4-17.8 g and 3.3-5.2 g respectively. Preliminary phytochemical screening revealed the presence of terpenoids, flavonoids, tannins and saponins.